Toxicity of Metals to a Freshwater Snail, Melanoides tuberculata. (24th April 2012) - Shuhaimi-Othman, M.; Nur-Amalina, R.; Nadzifah, Y.
Abstract : Adult freshwater snails Melanoides tuberculata (Gastropod, Thiaridae) were exposed for a four-day period in laboratory conditions to a range of copper (Cu), cadmium (Cd), zinc (Zn), lead (Pb), nickel (Ni), iron (Fe), aluminium (Al), and manganese (Mn) concentrations. Mortality was assessed and median lethal times (LT50 ) and concentrations (LC50 ) were calculated. LT50 and LC50 increased with the decrease in mean exposure concentrations and times, respectively, for all metals. The LC50 values for the 96-hour exposures to Cu, Cd, Zn, Pb, Ni, Fe, Al, and Mn were 0.14, 1.49, 3.90, 6.82, 8.46, 8.49, 68.23, and 45.59 mg L −1, respectively. Cu was the most toxic metal to M. tuberculata, followed by Cd, Zn, Pb, Ni, Fe, Mn, and Al (Cu > Cd > Zn > Pb > Ni > Fe > Mn > Al). Metals bioconcentration in M. tuberculata increases with exposure to increasing concentrations and Cu has the highest accumulation (concentration factor) in the soft tissues. A comparison of LC50 values for metals for this species with those for other freshwater gastropods reveals that M. tuberculata is equally sensitive to metals.